Identifying Factors Influencing Urbanization in Denpasar City - Gde Indra Surya Diputra; I Made Risma M. Arsha (Department of Development Economics, Universitas Sriwijaya, 2023)
Urbanization has both positive and negative impacts on an area. This study aims to analyze the relationship between GRDP, district minimum wages, and labor participation with urbanization in Denpasar City. The research method used is multiple linear regression analysis using GRDP data, district minimum wages and labor participation in 2010 - 2020 and processed with SPSS version 25.0 with a determined significance level of 95% (p <0.05). The results of the study show that the Gross Regional Domestic Product (GRDP), district minimum wages and labor participation affect urbanization partially and simultaneously with probability (p<0.05). Testing the level of correlation with the Adjusted R Square of 0.999 (99.9%) gross regional domestic product (GRDP), district minimum wages and labor participation have a very strong influence on urbanization in Denpasar City. Socio-economic disparities, inadequate infrastructure, low industrialization, low job availability, low wages, and inadequate social networks increase the desire for urbanization. The practical implication of this research is to increase economic growth and equity in controlled urbanization areas as a solution to accelerating economic development.